3x+12=x+3

Simple and best practice solution for 3x+12=x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+12=x+3 equation:



3x+12=x+3
We move all terms to the left:
3x+12-(x+3)=0
We get rid of parentheses
3x-x-3+12=0
We add all the numbers together, and all the variables
2x+9=0
We move all terms containing x to the left, all other terms to the right
2x=-9
x=-9/2
x=-4+1/2

See similar equations:

| 10-5u=-3u | | 0.3x-1.5=2.4 | | 7x-3=3x+3+4x | | 47=-10a+3a+12 | | -9=5n+4n | | 2(1.25y+3)=23.5 | | -4x-12x+2x=-30+46 | | a=-35/11 | | 5*x/2=12 | | 4(h-14)=16 | | -(c-8)=-152 | | 3(2x+2)=(3*2x)+(3*2)=6x+6 | | -0.8v+14=39 | | −9t+2=56 | | x+9/20=2x-2/15 | | |x-5|=21 | | 180=x+2x+x+7+2x-2+x+3 | | -20=-2x-4 | | 6x−3=−18+x | | (X+90)=7x | | -(h-14)=5 | | x+15.7=(-18.1) | | 12/18=x/100 | | 9y+8=8y-32+y | | m/3+2=18 | | 5a-4a+5=20 | | 2xxx=42 | | (-3)-4j=(-6j)+19 | | 2-8v=-10-10v-6 | | -4f+2(4f-52)=19 | | -6=3n=12 | | 6x+8-3x=3x-24 |

Equations solver categories